Regional products, regions’ reputation and commercial strategies: a tale of two cheese suppliers - Ribeiro, J. Cadima (2006)
Clustered SMEs in well defined geographical areas are producing and selling regional products to domestic and foreign markets. Most of the local activities are embedded in historical tradition and geographic, cultural and social specificity. To study the mechanisms and factors which favour spontaneous development in specific areas and make SMEs competitive, we used case study methodology. An evolutionary perspective of “Casa Matias” and “Casa dos Queijos”, two Portuguese SMEs, is expected to illustrate which key factors triggered the firm’s cheese business and, simultaneously, examine organisational practises, with particular emphasis on cluster formation and internationalisation process. From this analysis we expect to conceptualize a policy scheme to help developing spontaneous entrepreneurship, cooperation between clustered SMEs and policy-makers to establish more efficient and sustained regional and rural development strategies.